A strategy for in-house production of a positive selection cloning vector from the commercial pJET1.2/blunt cloning vector at minimal cost - Nawawi, Omar; Abdullah, Mohd Puad; Yusuf, Chong Yu Lok (SpringerLink, 2022)
DNA cloning technology requires a vector to harbour a gene of interest for multiplication of the gene in bacterial cells. Positive selection vector has become a popular type of cloning vector due to the simplicity and efficiency of the positive selection system. Due to the presence of a toxic gene, propagation of a commercial positive selection vector in common laboratory E. coli strains is infeasible. This study demonstrated a strategy for propagation and in-house production of a commercial positive selection vector, i.e., pJET1.2/blunt cloning vector, at low cost. This was done by insertion of a specially designed DNA fragment (MCS fragment), which can be easily removed later by EcoRV digestion, into the pJET1.2/blunt cloning vector to allow the propagation of the modified plasmid (termed pJET1.2M) in common E. coli strains. Removal of the MCS fragment from the pJET1.2M plasmid produces the pJET1.2/blunt cloning vector ready for gene cloning. The self-made pJET1.2/blunt cloning vector exhibited a cloning efficiency of 100%.